IL-1β knockout increases the intestinal abundancy of Akkermansia muciniphila - Bechberger, Maren; Eigenbrod, Tatjana; Boutin, Sébastien; Heeg, Klaus; Bode, K. A. (Beneficial microbes, 2023)
Abstract The proinflammatory cytokine interleukin-1β (IL-1β) is known to be upregulated in patients suffering from metabolic syndrome. IL-1β contributes to insulin resistance in obesity and type 2 diabetes, yet its influence on the intestinal microbiome is incompletely understood. The data presented here demonstrate that mice genetically deficient in IL-1β show a specific alteration of intestinal colonisation of a small group of bacteria. Especially Akkermansia muciniphila, a bacterium reported to be inversely associated with obesity, diabetes, cardiometabolic diseases and low-grade inflammation, showed increased colonisation in IL-1β knockout mice. In comparative microarray analysis from mucus scrapings of the colon mucosa of IL-1β knockout and wildtype mice, angiogenin 4 mRNA was strongly reduced in IL-1β knockout animals. Since the presence of angiogenin 4 in the culture medium showed a significant growth inhibition on A. muciniphila which was not detectable for other bacteria tested, IL-1β induced expression of angiogenin 4 is a strong candidate to be responsible for the IL-1β induced suppression of A. muciniphila colonisation. Thus, the data presented here indicate that IL-1β might be the lacking link between inflammation and suppression of A. muciniphila abundance as observed in a variety of chronic inflammatory disorders.